Secularization, Art and Religion or – What it is – San Sebastian? - Šerpytytė, Rita (Religija ir kultūra, 2010)
The article deals with the meaning of secularization as the challenge for contemporary world and considers the ways that secularization affects religion and art as well as their mutual relationship. Different concepts of the meaning of secularization are discussed and their ontological perspectives are highlighted. The attitude, that it is namely the ontological emphasis of the meaning of secularization that enables us to explain its challenge for contemporary world, is being justified. Based on this perspective, the relationship between religion and art in the contemporary world is analyzed and interpreted. The article also focuses on one of the tendencies of contemporary art, i.e. the tendency of conceptualization. Not only by interpreting certain works of art, but also elucidating different strategies of contemporary art, the “mutation” of the religious sense of “religious” art is disclosed. The analysis shows that the secularized meaning of art flourishes through its “alive” and “active” religious meaning. The conclusion is drawn that the analysis of the contemporary relationship between religion and art enables us to disclose the ambiguity of secularization – its sacral and profane sense, a certain dialectics of the process of secularization.
Keywords: secularization; art; religion; nihilism; Ch. Taylor; Vattimo